2012
DOI: 10.3109/03630269.2012.746942
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of the Hb E [β26(B8)Glu→Lys,GAG>AAG] Variant In Totos, One of the Smallest Primitive Tribes in the World

Abstract: Toto is one of the smallest tribes in the world. This primitive sub Himalayan, endogamous tribe lives in a small, isolated village called Totopara in the Jalpaiguri district of West Bengal in India. The tribal communities of West Bengal are vulnerable to various genetic disorders such as β-thalassemia (β-thal). We have studied 443 Totos to define their Hb E [β26(B8)Glu→Lys, GAG>AAG] status. Awareness and screening camps have been organized in various parts of Totopara during the last 2 years. We collected 3 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This in turn may increase the genetic load in terms of hemoglobin disorders through reduced level in infant and childhood mortality who will survive until their reproductive period for diagnosis and treatment. Once I hypothesized that together with demographic transition the frequency of the recessive genes like that of hemoglobin E may increase leading to genetic load in a population (Sikdar 2008a) and it became very much implicit with the studies among the Sonowal population of Assam (Barua and Kotal 2008) and Totos of West Bengal (Bhattacharyaa et al 2013). This type of conjuncture can further be established with the help of restudy of different population groups on different abnormal hemoglobin variants over a particular period of time.…”
Section: Hemoglobin E and Healthmentioning
confidence: 99%
“…This in turn may increase the genetic load in terms of hemoglobin disorders through reduced level in infant and childhood mortality who will survive until their reproductive period for diagnosis and treatment. Once I hypothesized that together with demographic transition the frequency of the recessive genes like that of hemoglobin E may increase leading to genetic load in a population (Sikdar 2008a) and it became very much implicit with the studies among the Sonowal population of Assam (Barua and Kotal 2008) and Totos of West Bengal (Bhattacharyaa et al 2013). This type of conjuncture can further be established with the help of restudy of different population groups on different abnormal hemoglobin variants over a particular period of time.…”
Section: Hemoglobin E and Healthmentioning
confidence: 99%
“…Toto is the smallest, particularly vulnerable tribal group in West Bengal 18 . The Toto population has been distributed in the many pockets of Alipurduar and New Jalpaiguri districts of West Bengal 19 , as well as in the border area of Bhutan 20 , because of their economic activities. Due to the COVID pandemic, the Toto population was getting restricted in a village called Totopara.…”
Section: Target Populationmentioning
confidence: 99%
“…Previous literature has shown that Totos have faced a double burden of different communicable and non-communicable diseases like metabolic syndromes 51 , tuberculosis, malnutrition 52 , malaria, smallpox, and skin problems, like other tribal populations in the hilly terrain of the Himalayan belt 53 . Apart from that burden, the shortfall of healthcare infrastructure was worse than the scarcity.…”
Section: Poor Health Care Issues Faced By Toto Populationmentioning
confidence: 99%
“…The sequence was compared with the sequence of the Human Genome Mutation Database (HGMD) and the National Centre for Biotechnology Information (NCBI). Haplotype analysis was performed using restriction fragment length polymorphism-PCR (RFLP-PCR) following the standard protocol described in our previous publication [6]. Six restriction endonuclease sites (HindII 5'ε, HindIII G γ, HindIII A γ, HindII 5' Ψβ, HindII 3'Ψβ, and Hinf I 3'β) within the β globin gene cluster were studied to construct the haplotype linked with this mutation.…”
Section: Methodsmentioning
confidence: 99%